Bentuk Pertanggungjawaban Pelanggaran Ham Terhadap Tawanan Perang Menurut Hukum Dan Ham Internasional - Figur Muhammad Ali Putra Nirwan; Josina Augustina Yvonne Wattimena; Arman Anwar (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The Syrian conflict was motivated by the Arab Spring, which was related to demonstrations and popular resistance in the Middle East and North Africa which ended with the fall of the ruling regimes in these regional countries.Purposes of the Research: The research method uses a normative juridical method. This type of research is descriptive analytical using primary, secondary and tertiary sources of legal materials where the collection of legal materials is carried out using library research. Furthermore, the analysis technique uses qualitative analysis, by identifying facts, eliminating irrelevant things, determining the issue and then concluding the results of the analysis according to the problem being studied.Methods of the Research: The research method uses a normative juridical method. This type of research is descriptive analytical using primary, secondary and tertiary sources of legal materials where the collection of legal materials is carried out using library research. Furthermore, the analysis technique uses qualitative analysis, by identifying facts, eliminating irrelevant things, determining the issue and then concluding the results of the analysis according to the problem being studied.Results of the Research:  Legal violations against prisoners of war based on international legal and human rights instruments according to the Geneva Convention III of 1949 (Geneva  Convention (III) Relative to the Treatment of Prisoners of Wat) and Additional Protocol I year 1977 (Protocol Additional to the Geneva Conventions of 12August 1949, and relating to the Protection of Victims of international Armed Conflicts) have the right to be treated with dignity and humanity, such as not being forced to provide information unless they know their identity. Their torture and cruel treatment is seen as a war crime. prisoners of war must be moved from dangerous areas to safe places. Their living conditions must be equivalent to those of members of the armed forces of the host nation. Accountability for legal violations against prisoners for serious human rights violations against prisoners of war legally basically refers to the principle of exhaustion of local remedies through the mechanism of a national court forum. The unwillingness and inability of countries suspected of committing serious violations of human rights to resolve the problem of these violations at the national level can underlie the emergence of the judicial competence of the International Criminal Court (ICC). War crimes and crimes against humanity in accordance with the Rome Statute (Article 5 paragraph (1).